Risk Factors for Eating Disorders among Male Adolescent Athletes - PUSTIVŠEK, Suzana (Zdr Varst, 2014)
OBJECTIVE: Eating disorders (ED) are an important and increasing problem in adolescents. The objective of this study was to examine the risk factors and the prevalence of risk for ED among male adolescent elite athletes and nonathletic controls. Differences between male athletes competing in aerobic, anaerobic and aerobic-anaerobic sports were examined as well. METHODS: This was a cross-sectional epidemiological study. A cross-sectional questionnaire survey and anthropometric measurements were conducted on 351 adolescents (athletes n = 228; controls n = 123). All participants were aged 15–17 at the time of measuring. Risk for ED was determined using a SCOFF questionnaire. RESULTS: The overall prevalence of the risk for ED in male adolescents was 24.8%, with no significant differences among athletes and controls or different subgroups of athletes (p>0.05), although the highest prevalence (37.2%) was registered in aerobic subgroup of athletes. Higher number of attempts to lose weight was associated with increased risk of ED in each group (athletes and controls). Other predictors referred to lack of breakfast and body composition in aerobic subgroup of athletes and number of meals and training frequency in anaerobic subgroup. The most common reasons for dieting were improvement of sport results (19.6–44.2%) and better self-esteem (41.5%) in athletes and controls respectively. CONCLUSIONS: Participation in the competitive sport itself is not associated with the increased risk for ED. It seems that risk factors for ED for adolescent athletes competing in aerobic and anaerobic sports represent a subject that deserves consideration and further investigation in the future.